EPISTEMOLOGI RASIONALISME RENE DESCARTES DAN RELEVANSINYA TERHADAP PENAFSIRAN AL-QUR`AN - Arifin, Mochammad (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
This article discusses about rationalism epistemology by Rene Descartes—modern philosopher—and his relevance to the Qur`anic exegesis. A study about epistemology is the perspective which is urgent in developing science in the future. The meaning of epistemology is the science methodology to express the rasionalism by Rene Descartes from the source, methods, and validity. This study found that the sources of rationalism by Rene Descartes is rationality; the methods of rasionalism is doubtful, intuition and deduction; the validity is measured by coherence theory. The result of this study has relevance to the Qur`an exegesis. The relevance is in the rationality, or in Qur`anic exegesis it is called tafsīr bi al-ra`yī or tafsīr bi al-‘aqlī. This interpreting isn’t only answer the issue which is up to date, but also as a new way in approaching the Qur`an through modern social sciences, like hermeneutica, stilistica, antropology, sosio-linguistic, and fenomenology.